Academic resilience among undergraduate students: The analysis of psycho-social and religious aspects - Julaihah, Umi; Achmad, Itsna Laily Rosyida; Sasi, Wahyuning; Zahro, Nikmatus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The increasing phenomena of mental health problems experienced by students need more attention not only by the parents but also by educational institutions and the government. Thus, we need a strategy to strengthen academic resilience, especially for students who are completing their thesis. In line with that, the aim of this study is to investigate the determinants of academic resilience. The independent variables proposed in this research are academic self-efficacy, social support and religiosity. This study applied a quantitative method with regression analysis using a questionnaire. One hundred twenty-eight completed responses were obtained from a state university in Malang, Indonesia. The research findings showed that only academic self-efficacy and social support have positive and significant effects on academic resilience. Although this study cannot confirm that religiosity has an impact on academic resilience, this research has attempted to fill the gap in previous research by elaborating on the determinants of academic resilience from psycho-social factors and religiosity.